Examining the domain-specificity of language mindset: a case of L2 reading comprehension. Issue 3 (27th May 2022) - Khajavy, Gholam Hassan; Pourtahmasb, Fereshteh; Li, Chengchen
ABSTRACT : Purpose: The present study investigated the domain-specificity of language mindset with a focus on foreign language (L2) reading mindset. We further examined whether L2 reading mindset could predict several L2 reading-specific outcomes, including L2 reading achievement and L2 reading emotions above and beyond general language mindset.Design/methodology/approach: We gathered data from 489 Iranian university students during regular classroom hours. Participants completed the questionnaire which included L2 reading mindset, general language mindset, L2 anxiety, and L2 enjoyment items. They further took an L2 reading comprehension test. Findings: Results of the confirmatory factor analysis supported a two-factor solution for both L2 reading mindset and general language mindset scales, corresponding to the fixed and growth categories. Furthermore, the findings of hierarchical multiple regressions indicated that adding L2 reading mindsets significantly added to the explained variance in L2 reading anxiety, L2 reading enjoyment, and L2 reading achievement. Originality/value: Findings of this study supported the incremental validity of L2 reading mindset as it could predict L2 reading outcomes above and beyond general language mindset. This finding empirically supports the domain-specificity of language mindset. Therefore, both L2 researchers and teachers should be aware of the unique role that L2 reading mindset plays in L2 reading skill.